The Association Between Camellia sinensis Tea Consumption and Reduced Risk of Anxiety Disorder for Covid-19 Survivors: A Cross-Sectional Study among Medical Students - Mohammad Bakhriansyah; Vina Yulia Anhar; Sidnan Naufa Sulaiman; Faishal Muhammad Arrosyad (Berkala Kedokteran, 2023)
Abstract: